Explorers or Exploiters: A Multi-Technique Bibliometric Review of Individual Ambidexterity - Kitanovikj, Bojan; Eftimov, Lјupcho; Cvetkoska, Violeta (Academy of Management Proceedings, 2025)
Global and dynamic environments have pressured organizations into becoming more ambidextrous, resulting in a paradox for contemporary organizational sciences (Papachroni & Heracleous, 2020; Zhang et al., 2022). While employees are seen as a key driver of competitive advantage and high organizational performance, their ambidexterity, i.e. individual ambidexterity has remained in the margins of the research landscape (Nasution et al., 2024; Parmigiani & Howard-Grenville, 2011). This single-perspective research lens neglects the diverse experiences and characteristics of each individual and the ways they can influence the balance between exploration and exploitation as organization members. Recently, researchers have answered the call with several studies analyzing the antecedents and outcomes of individual ambidexterity as well as this concept’s interplay with other organizational phenomena (Schnellbächer et al., 2019). Still, as a growing research niche, which is critical for understanding modern workplaces, there is a lack of a comprehensive, bibliometric synthesis of the findings and an analysis of the gaps. To address this, our research provides a comprehensive, multi-technique bibliometric review of individual ambidexterity research, identifying key trends and underexplored areas in the field. Individual ambidexterity in the organizational context is gaining momentum as a crucial component of innovative behavior and performance, individual well-being, as well as team ambidexterity, firm performance, and organizational sustainable outcomes (Mu et al., 2022; Akbar et al., 2024). Considering the context of rising flexible and remote work arrangements and the growing accessibility and use of artificial intelligence, there has never been a more important time to investigate the genesis and core of employee ambidexterity. This environment underpins the need for lifelong learning, flexibility, reskilling, and upskilling for individuals to stay relevant in their roles, which challenges how we view this type of ambidexterity (Balzano et al., 2024). Essentially, it is conceptualized as the individual ability to simultaneously explore and exploit organizational resources, or, in other words, to perform contradictory activities by switching mindsets and action sets (Rogan & Mors, 2014), presenting a paradox for managers and decision-makers. Thus, our study aims to contribute by integrating the knowledge about individual ambidexterity and pointing out hotspots, influential scientific voices, and areas for further investigation using a multi-technique bibliometric approach, grounded in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Stemming from this, central to this research investigation are the following research questions: 1) What is the inherent intellectual structure of the individual ambidexterity body of research? 2) What are the most impactful hotspots and themes in the research landscape? 3) What is the potential of individual ambidexterity research and what literature gaps on the topic exist?